Analysis of the using ChatGPT as Coping Stress - Tuanany, Umurdin Syafrandy; Talqis Nurdianto (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Stress is a common problem that is often discussed because of its connection to mental health. Even so, stress is often not taken seriously. In fact, this disease can attack anyone, be it the elderly, the younger generation, workers or students. Academic literature studies show that stress also occurs in students because of the large and ever-increasing workload. In managing stress, it is important to learn effective coping mechanisms. That way, stress does not become a burdensome pressure. In today's world, technology has become a popular solution for dealing with stress, especially through social media and other forms of technology. ChatGPT is an AI system that can communicate with humans naturally. The aim of this research is to find out whether using the ChatGPT function can help relieve stress in final year students who are working on their thesis in the Arabic Language Education program at Muhammadiyah University of Yogyakarta. The research method applied here is descriptive qualitative, and data was collected through questionnaires. Data was collected, reduced and presented narratively.